EARNING MANAGEMENT DAN GOOD CORPORATE GOVERNANCE TERHADAP INTEGRITAS LAPORAN KEUANGAN - Firjatillah Bulan Azari (2022)
This study is a quantitative study that aims to determine the effect of earnings management, audit committee, and independent commissioners on the integrity of financial statements. The integrity of financial statements is measured using the Beaver and Ryan model. The sample in this study was 14 BUMN companies listed on the Indonesia Stock Exchange, especially the main board in the 2016 - 2020 period. The hypothesis testing in this study used multiple linear regression analysis with the SPSS version 25 assistance program with a significance level of 5%. The results of the test are (1) earnings management has a positive effect on the integrity of financial statements, (2) the audit committee has a positive effect on integrity of financial statements, and (3) independent commissioners have no effect on the integrity of financial statements.